A clinical comparative study of ropivacaine versus ropivacaine with fentanyl by continuous epidural infusion for post-operative analgesia and ambulation in patients undergoing major gynecological surgery - Pathak, Nidhi; Tiwari, Tanmay; Singh, Sweta; Manik, Yogesh Kumar; Dhama, Vipin Kumar; Dahiya, Subhash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To compare the effect of continuous epidural infusion of ropivacaine versus ropivacaine-fentanyl for post-operative analgesia and ambulation in patients undergoing major gynaecological surgeries.Methods: A total of 60 patients of age 20 to 50 yrs of body mass index (BMI) within normal range (18.5to24.9 kg/m2) posted for major gynecological surgeries were divided into two equal groups (Group R and RF) in a prospective, randomized, double-blind fashion. In Group RF (n=30) 0.1% Ropivacaine with 2µg/ml Fentanyl and in Group R (n =30) 0.1% ropivacaine were used. General anaesthesia was given to all patients. Continuous epidural infusion using elastomeric pump was started at ‘0’ post-operative hours at 6ml/hour. Post -operative pain (Visual Analogue Scale Score), ambulation (James Modified Bromage Scale) and side effects were noted at 0, 2, 4, 6, 12, 18, 24, 36 and 48hrs.Results: The differences in VAS Score of subjects of both the groups were statistically significant(p<0.05) at 18 hrs, 24hrs, 36hrs and 48 hrs and the differences in Modified Bromage Scale of subjects of the groups were statistically similar at most of the time intervals. Also, the side effects were statistically similar between the groups.Conclusions: Author concluded that ropivacaine-fentanyl is better than ropivacaine alone by continuous epidural infusion for post-operative analgesia in major gynecological surgeries with no statistically significant side effects, effect on ambulation being similar in both the groups.